Crisis Communication Model in Relational Conflicts Between Corporations and Local Communities - Putri, Nurfia Devi Friesta (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2025)
The rejection of PT Indofon’s new factory construction in Taruban Kulon Hamlet reflects a relational crisis triggered by the lack of early socialization and community involvement during the project planning phase. This study aims to analyze and formulate a relevant and applicable crisis communication model for Indofon to strategically and sustainably prevent, respond to, and restore social relations with the local community. The model refers to Situational Crisis Communication Theory (SCCT) and Expectancy Violation Theory (EVT). This research employs a qualitative approach using a case study method. The findings reveal that during the crisis phase, Indofon undertook several efforts to mitigate tensions, including internal communication coordination, formation of a crisis communication team, appointment of a spokesperson, crisis message delivery, strategic meetings with village officials, participatory dialogue (discussion), public commitments and implementation, and evaluation. Based on SCCT, Indofon adopted a rebuild strategy by offering a formal apology (apology strategy) and providing both written and unwritten compensation (compensation strategy). Furthermore, although categorized within the intentional cluster, Indofon also applied an attack the accuser strategy typically found in the victim cluster by confronting parties making negative claims. This study contributes a crisis communication model based on community expectation mapping, consisting of five stages: crisis preparedness, stakeholder mapping, crisis diagnosis, announcement and implementation, and evaluation with contingency planning